Neogene stress pattern evolution along the semangko fault, sumatra - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT Western Indonesia corresponds to the subduction of the Indo-Australian plate beneath the Eurasian plate. The convergence between the two plates is oblique along the Sumatra trench. The1650-km-long, dextral Great Sumatran fault has been considered to accommodate the lateral component of convergence. The Semangko fault is the southern segment of the Great Sumatran fault, striking NW-SE, from the Suwoh caldeira to. the Semangko Bay. Fault kinematic analysis along the Semangko fault suggests that three successive tectonic periods have occurred from late Miocene to Present. The older one corresponds to strike-slip deformation that took place prior to the end of Miocene and which were characterized by a N-S trending compression. This strike-slip deformation is followed by a roughly NE-SW trending extension perpendicular to the Sumatra trench, since 5 My. Finally the younger (Quaternary) tectonic period correponds to an E-W trending extension that is still seismically active. These three tectonic periods appear to correspond to two very different stress regimes. The first one should be characterized by strong plate coupling that would produce dextral slip on the Semangko fault and WNW-ESE extension in the areas of pull-apart and specially on the termination of this strike-slip fault. The second one should be characterized by weak plate coupling and would be responsible for NE-SW extension on the Semangko fault. The obtained results show that the stress pattern associated with a - major strike-slip fault is unstable.